Dental Anxiety Impact on Oral Health Related Quality of Life: A Cross-Sectional Study in Benghazi, Libya - Abdelnabi, Abdelmonem; Rafeeq Al Kuwafi,; Sara Bushwigeer,; Fatma Ahdash, (AlQalam Journal of Medical and Applied Sciences, 2025)
Dental anxiety (DA) is a common condition associated with subsequent health-related and psychosocial outcomes. The sense of well-being and satisfaction with daily performances influenced by dental and oral conditions is known as oral health-related quality of life (OHRQoL). This study aimed to evaluate the impact of dental anxiety on quality of life in Benghazi city. The basic research design included a cross-sectional study involving a randomly selected sample of the Benghazi population (N=717, age = 16 – 72 years old). The data was collected by means of a questionnaire on Google Forms online and printed handouts. Statistical analyses were made with descriptive statistics, inference t- test and chi-square using IBM SPSS Statistics version 22.0. Among the study group, 64.2% were females and 35.8% were males. Based on the MDAS score, 15.8% of the participants were identified to be highly anxious and suffering from dental phobia. Generally, more female participants 72% had dental phobia than males. There were significant differences between the phobic group's and non-phobic group's Oral Health Impact Profile-5 (OHIP), with phobic participants having generally higher scores. Dental anxiety is associated with the impact oral health has on life quality; participants experiencing high levels of dental anxiety were mostly females and had poorer oral health‐related quality of life than those who didn't.